Mexican politics in transition - Gentleman, Judith, 1950- (Routledge, Taylor & Francis Group, 2018)
Initiated in the mid-1970s, Mexico's program of political reform was designed to provide a new opportunity for political competition. In this book, contributors examine the significance political mobilization has had and the extent to which the reform has served as a vehicle for defusing discontent in the wake of Mexico's failed oil-based developme